Analysis of UT Student Satisfaction with the Tuweb system using CSI, IPA & SEM-PLS - Masakazu, Kadek; Sopandi , Agus Tatang; Wijaya, I Gusti Ngurah Satria; Suwardika, Gede; Suniantara, I Ketut Putu (LPPM Undiksha, 2023)
One form of development in the world of learning as a result of developments in information and communication technology (ICT) is that distance learning is possible. The Open University, a public university, uses various modes of learning has also experienced changes in the modes of learning for students who decide to study in person during class. Coupled with the Covid-19 pandemic, this change is a change in the learning system from the TTM mode which is replaced by Tuweb (blended learning that is held online). This study aims to analyze user or UT student satisfaction with the Tuweb system using the Servqual dimension. The data source came from the UT student population at UPBJJ UT Denpasar, where the determination of respondents was carried out using a purposive sampling technique. The Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), and Structural Equation Modeling (SEM) using Partial Least Squares (PLS-SEM) are the analytical techniques used. The results of the slices of the three methods (CSI, IPA and SEM-PLS) is that Tuweb UT's services get quite satisfied ratings from students, where the variable that gives excellence to Tuweb UT is empathy. As a note for improving the tuweb service from UT, the Tuweb service has the availability of a learning service response at any time and place (responsiveness variable) and the Tuweb service has better speed accuracy than the promised speed accuracy (reliability variable).